Experimental Study on Seismic Performance of New RCS Connection. (February 2017) - Nguyen, Xuan Huy; Nguyen, Quang-Huy; Le, Dang Dung; Mirza, Olivia
Abstract: This paper deals with an experimental study on seismic performance of a new type of exterior RCS connection, in which a steel profile embedded inside RC column is directly welded to the steel beam. A full scale exterior hybrid joint was built and tested under reversed-cyclic loading at the University of Transport and Communications of Vietnam. Seismic performance in term of load bearing capacity, story drift capacity, ductility, energy dissipation and stiffness degradation were evaluated. The test specimen showed a good response to cyclic load reversals. The experimental results indicated that the test specimen performed in a ductile manner and the stiffness degradation during the cycles performed was gradual. It was concluded that the studied RCS joint could be used as dissipative element in the structures of ductility class medium (DCM).